P-078 Enteral Feeding Therapy for Maintaining Remission in Crohn's Disease: A Systematic Review. (March 2016) - El-Matary, Wael; Otley, Anthony; Critch, Jeff; Abousetta, Ahmed
Abstract : Background: Exclusive Enteral nutrition (EN) therapy can be utilized as a primary treatment for active Crohn's disease (CD) and is considered as the first-line of treatment for CD in children, especially in Europe and Japan. The efficacy of supplementary EN for maintaining remission in patients with inactive CD is unclear. The aim of this work was to systematically identify, review and critically appraise the evidence of the efficacy and safety of EN in maintaining remission for patients with inactive CD. Methods: We searched PubMed/MEDLINE (National Library of Medicine), EMBASE (Ovid), and Cochrane Central Register of Controlled Trials (CENTRAL, Wiley) from inception till April 2015 for relevant citations of published randomized controlled trials (RCT) and cohort studies using individualized search strategies prepared for each database. The primary outcome was relapse rate in patients with inactive CD who have been in medically induced remission and subsequently started or maintained on EN for maintaining remission. Results: Twelve studies, included 1169 patients, fulfilled the inclusion criteria with 3 adult RCTs and 2 pediatric observational studies included. Out of 730 patients who were given supplementary EN to maintain remission, 341 (46.7%) (95% CI 42.4%–49.6%) patients experienced first relapse compared to 281 (64%) (95% CI 59.5%–68.4%) out of 439 patients in the non-EN group ( P < 0.01). The adult studies included 1074 patients with inactive Crohn's disease. The crude pooled relapse rate in the EN group was 47% (95% CI 43.3%–50.7%) compared to 64% (95% CI 59.2%–68.8%) in the non-EN group ( P < 0.01). Only one high-quality adult RCT was found with a relapse rate of 34.5% in the EN group compared to 64% in the regular diet group ( P < 0.01) after a mean duration of follow up of 11.9 months. For the 2 pediatric observational studies, the crude pooled relapse rate in the EN group was 42% (95% CI 27.2%–56.8%) compared to 63.5% (95% CI 49.9%–76.1%) in the non-EN group ( P = 0.04). Although lack of compliance with EN intake was documented in few studies, no major adverse events were reported in patients taking EN. Conclusions: Compared to regular diet, the current evidence suggests that EN is safe and effective in maintaining remission for patients with inactive CD. Large properly designed randomized controlled studies are required to confirm the efficacy of supplementary enteral nutrition compared to individual medications such as immunomodulators and biological medications in maintaining remission in CD.